The relationship between knowledge of socio scientific issue and nature of science in ecosystem material in high school students - Ilmi Octaviani Geopany; Diana Hernawati; Vita Meylani (Biosfer: Jurnal Pendidikan Biologi, 2021)
The purpose of this study was to know the relationship between socio-scientific issues with nature of science students in ecosystem material of the XI Math and science class in one of the High Schools. This research was conducted from September- October 2020. The type of research was correlational with sample of 36 students taken using a purposive sampling technique as evidenced by the average value of daily tests. The technique on data collection was a non-test instrument socio-scientific issue questionnaire and essay test the nature of science. The research instruments used included a socio-scientific issue questionnaire which states 13 statements regarding controversial issues regarding ecosystems and the views nature of science form B (VNOS-B) description test to measure the nature of science dictated by Lederman et al. (1998) and have settled 14 questions. Data were analyzed using Pearson bivariate. The results of this study obtained a significance of 0.00 < (0.05) which indicates the relationship between socio-scientific issues with the nature of science and 0.729 as the display value. This analysis concludes that there is a positive relationship between socio-scientific issues with the nature of science at a high level. Teachers are expected to be able to improve skills in indicators of socio-scientific issues, one of which is by training sensitivity and awareness of environmental problems that students encounter on a daily basis.